Production and purification of B-Mannanase from Bacillus subtilis M7 - Nuttapong Saetang (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Bacillus subtilis M7 is a lipase defective mutant strain obtained by X-ray mutagenesis of B. subtilis MR10. The bacterial strain has been developed for using as the β-mannanase producer for application in mannooligosaccharide production from β-mannan in copra meal. In this research, B. subtilis M7 was investigated for the capability of β-mannanase production for application in the MOS production. The most suitable inorganic nitrogen and organic nitrogen sources for β-mannanase production were ammonium sulphate and soybean meal, respectively. Screening for the influential ingredient affecting on enzyme production by Plackett and Burman experimental design was performed and the result indicated that only copra meal was the positive significant factor influenced on the β-mannanase productivity (P< 0.05). The optimal concentration of copra meal for enzyme production was investigated and it was found that copra meal 6.0 g/l gave the highest β-mannanase activity with other ingredients of 5 g/l soybean meal, 0.3 g/l K2HPO4, 1 g/l KH2PO4, 1 g/l CaCl2.2H2O, 0.05 g/l ZnSO4.7H2O, 2 g/l (NH4)2SO4 and 0.2 g/l MgSO4.7H2O, initial pH 6.8. Time course study of enzyme production using the optimal medium found that the bacterial strain produced β-mannanase 12.65 U/ml at 30 h cultivation. In addition, the activities obtained from the optimized medium with locust bean gum and konjac flour were higher than the activity that of copra meal approximately 2.3 folds. The optimum condition for B. subtilis M7 β-mannanase production was an initial pH range of 6.8-7.0 and 37°C. Moreover, the β-mannanase production using optimized medium in a 5-L bioreactor at 37°C for 30 h found that higher agitation rate at 400 rpm gave the higher enzyme activity of 16.51 U/ml, which was more than the activity obtained at 200 rpm and from laboratory scale approximately 1.26 and 1.30 folds, respectively. Furthermore, addition of 3% (w/v) sodium chloride to crude β-Mannanase solution enhanced the enzyme stability as 94% of its initial activity after stored at 4°C for 42 days. β-Mannanase from B. subtilis M7 was purified to apparent homogeneity by ion-exchange chromatography and gel filtration chromatography. The purified enzyme is a single band of protein with molecular weight of 42 kDa. The optimum temperature and pH of β-mannanase activity was 50-60°C and pH ranging from 5.0-7.0. It was stable for 24 h at 4°C between pH 4.0 and 9.0, and for 1 h up to 60°C. The enzyme showed high specific requirements for Co2+, Mn2+, Fe3+, Al3+ ions and mercaptoethanol, to enhance enzyme activity. It was found that the enzyme was the metal-dependent enzyme. The Michaelis-Menten constants (Km), and maximum velocity (Vmax) values were 30.34 mg/ml and 1347.76 µmole/min/ml, respectively. Furthermore, the pattern of MOS from copra meal hydrolysis by purified enzyme was similar to MOS obtained from locust bean gum hydrolysis. However, the quantity of MOS products from both substrates was different.